تأثير نظام الاتصالات في مشاركة المنظمات بالمعرفة الموجهة نحو الميزة التنافسية : دراسة تحليلية لآراء العاملين في عينة من المستشفيات الاهلية بالموصل - وزيرة محمد يحيى (PROSPECTIVE RESEARCHES, 2023)
This research aimed at testing the effect relationship, which is shown by organizations participation in knowledge in enabling the organizations to acquire the competitive advantage within the support that may be presented by communication system to this participation. After preparing suitable definition for the variables of her research (communication system, participating knowledge and competitive advantage) the author tested the mentioned relationship on correlation and effect levels. This is achieved by using the data obtained by the questionnaire prepared for this purpose and distributed to the members of the sample working in (AL_Zahraoy, AL_Rabeigh, and Ninauah hospitals) totaled (45) workers. The study led to several conclusions that emphasize the researcher’s point of view that communication system can support knowledge participation and that can enhance its role in enabling. The organization to equire the competitive advantage in its environment, So based on these conclusions, the researcher presented her suggestions that motivate managers in the studied organizations to pay attention to communication system and knowledge participation as their organizations concerned due to its importance in achieving organizations goals in field of competitive advantage.